Effect of parameters and surface analysis on eglin steel by shot blasting method. (2023) - Srinivas Reddy, P.; Ravi Kumar, P.; Prasad, D.V.S.S.S.V.; Saroja Rani, Bh.; Narayana Gupta, CH.LDS.; Daniel Das, A.; Subbiah, Ram
Highlights: The different factors of shot blasting process and their effect on surface roughness (Ra) were analyzed. The surface roughness were evaluated based on the different input constrains such as blasting angle, standoff distance (SoD) and blasting time. The effect of surface roughness and its analysis were conducted on eglin steel. The surface topography was analyzed before and after the shot blasting process using atomic force microscopy (AFM). Abstract: The surface finish is progressively improved by shot blasting method. The present work describes the different factors of shot blasting process of eglin steel and their effect on surface roughness (Ra). The surface roughness were evaluated based on the different input constrains such as blasting angle, standoff distance (SoD) and blasting time. The surface topography of the eglin steel was analyzed before and after the shot blasting process using atomic force microscopy (AFM). The optimal shot blasting parameter is attained through Taguchi method. The effect of parameters on surface roughness and their contribution were validated by analysis of variance. It was concluded that the surface roughness was greatly improved after shot blasting process. The optimal surface roughness was performed at 900 mm of standoff distance, 60 degree of blast angle and blasting time of 50 s. The excellent surface was attained after shot blasting process of eglin steel with average roughness is 14.15 nm.